Swash zone morphodynamic modelling including sediment entrained by bore-generated turbulence - Zhu, Fangfang; Dodd, Nicholas (2020)
In this paper we introduce a mathematical model of sediment entrainment due to bore-generated turbulence in a shallow water context. In this model, the entrainment is assumed to be proportional to the energy decay rate across a bore on a mobile bed. The energy decay rate across a bore on a mobile bed is derived analytically. This model is incorporated into the one dimensional morphodynamic model developed by Zhu and Dodd (2015), which includes bed- and suspended load transport. This results in new shock conditions, which allow for sediment entrainment at a shock. With it we investigate the effects of sediment entrainment due to bore-generated turbulence on beachface evolution under a single swash event driven by a solitary wave. The simulation results imply that sediment entrainment by bore turbulence at the incoming bore dominates over sediment mobilisation by bed shear stress. In contrast, the backwash bore is dominated by bed shear stress related processes. The morphodynamic impact of bore turbulence on this swash event is primarily erosion of the sea bed seaward of the initial shoreline. Any sediment remaining in the water column seaward of this point is then available to be transported by subsequent events. It is shown that the bed step is primarily a bed load related feature, with sediment entrained as suspended load counteracting the bed step growth.